Parental concern of feeding difficulty predicts poor growth status in their child - Way Seah Lee; Chun Wei Tee; Aaron GS. Tan; Shin Yee Wong; Kee Seang Chew; Hon Kit Cheang; Tammy Lim; Lucy CS. Lum; Marion Margaret Aw (Pediatrics and Neonatology)
Background: Parents often express concerns about feeding difficulties in their child. We hypothesized that these parental concerns were associated with adverse growth status in early childhood. We aimed to determine the prevalence of such concerns and whether these concerns were associated with adverse growth status in early childhood. Methods: We performed a cross-sectional study among healthy children aged 12–36 months attending three well-baby clinics in three urban areas in Malaysia and Singapore between December 2016 and February 2017. Parents were interviewed for concerns about their child's feeding and presence of behavioral and organic red flags for feeding difficulties. We defined growth faltering as weight-for-age < 3rd centile and short stature as height-for-age < 3rd centile according to World Health Organization Growth Standards. Results: Of the 303 children studied (boys = 160, 52.8%; mean [± SD] chronological age at interview 21.3 [± 4.0] months), 13% (n = 38/292) had growth faltering and 19.5% (n = 50/256) had short stature. Overall, 36.3% (n = 110) of parents expressed concerns about their child's feeding behavior. Sixty-eight percent (n = 206) of parents reported presence of at least one behavioral and 18.5% (n = 56) had at least one organic red flag for feeding difficulties, respectively. 9.9% (n = 30) had both behavioral and organic red flags for feeding difficulties. Growth faltering was significantly associated with parental concern about feeding (odds ratio [OR] 3.049, p < 0.001), food refusal (OR 4.047, p < 0.001) and presence of at least one organic red flag (OR 2.625, p = 0.012). Conclusion: We found that parental concerns about their child's feeding to be common. Presence of parental concern, food refusal in the child and presence of organic red flags for feeding difficulties are associated growth faltering in early childhood. Key Words: feeding difficulties, growth faltering, parental concerns